Mastering Bootstrap 4 - Second Edition - Benjamin Jakobus; Jason Marah (Packt Publishing, 2018)
Mastering Bootstrap 4 takes you step-by-step through building professional-quality, responsive web applications using the powerful Bootstrap 4 framework. With this book, you will learn how to effectively use Bootstrap's grid system, styles, components, and plugins to create customized interfaces that work seamlessly across devices.What this Book will help me doDevelop a responsive website from scratch using Bootstrap 4, ensuring optimal design for various devices.Understand and apply the Bootstrap 4 grid system to construct intricate and adaptive layouts.Learn to utilize and customize Bootstrap's built-in components, such as navigation menus and form elements.Integrate Bootstrap with JavaScript frameworks like Angular and React to create dynamic, modern web apps.Explore methods for creating and using custom plugins to extend the functionality of your Bootstrap web applications.Author(s)The author is an experienced web developer and educator who has spent years mastering Bootstrap and its integration with modern web technologies. With a passion for teaching complex technical subjects in a clear and practical manner, the author ensures readers can confidently apply the concepts to real-world projects. This book reflects their commitment to making web development accessible and rewarding for everyone.Who is it for?This book is ideal for web developers looking to create responsive and visually appealing web applications. If you have foundational knowledge of HTML, CSS, and JavaScript, and wish to learn Bootstrap 4's capabilities for designing modern web interfaces, this book will guide you step-by-step. Whether you aim to design custom layouts or integrate Bootstrap within advanced frameworks like Angular or React, this resource aligns perfectly with your goals.